Changes in ecological, agricultural, and urban land space in 1984–2012 in China: Land policies and regional social-economical drivers. (January 2018) - Wang, Jing; He, Ting; Lin, Yifan
Abstract: Researches on land changes and ecosystem services from the perspective of global and regional ecosystems have received a worldwide attention in recent years. Land space refers to a cluster of adjacent land-use units with similar functions and uses and disturbance characteristics at various scales. However, few studies has focused on synthesizing ecological, agricultural, and urban land space changes and their socio-economic driving factors at national scale using partial least square regression ( PLSR ) analysis method based on accurate and reliable data from national land surveys. The paper analyzed the spatial-temporal changes and regional differentiation of ecological, agricultural, and urban land space in China and discussed the impacts of land policies on these changes and identified the key regional socio-economic driving factors with variable importance in projection ( VIP ) value. Results indicated that ecological and agricultural land space decreased by 0.85% and 0.68% from 1984 to 2012, respectively; while urban land space increased by 1.53%. The changes in land space were characterized with spatial-temporal differentiation, mainly driven by economic level and land policies implementation. Chinese last 30 years' economic development mode has not been sustainable for rapidly consumption of ecological and agricultural land space. From 1984 to 2005, the area of ecological land space decreased in some regions and periods but increased in other regions and periods. However, from 2005 to 2012, the area of ecological land space decreased in all regions, with high rates in Jiangsu-Zhejing-Shanghai (JZS) and Beijing-Tianjin-Hebei (BTH) regions. From 1984 to 2012, the area of agricultural land space generally decreased in all regions but Qinghai-Tibet (QT) region, while the area of urban land space increased in all regions. Change rates of three types of land space were generally high in the 1984–1996, 2000–2005, and 2009–2012 periods and especially in JZS region. On one hand, national and regional land policies resulted in the temporal-spatial differentiation of these changes. Regional difference of socio-economic variables was one important character of changes in ecological, agricultural and urban land space. Fixed asset investment, economic density, and per capita GDP had important effects on the changes in ecological, agricultural and urban land space. On the other hand, there were some problems and deviations for some land policies. It is necessary to optimize land spatial pattern in different regions from ecological perspective. A zoning control system and differentiated land policies and natural ecosystem protection must be implemented in China. Highlights: Spatio-temporal changes in ecological, agricultural, and urban land space were quantified from 1984 to 2012. Rapid urbanization and land policies induced an unbalanced decrease of ecological and agricultural land space. Regional difference of socio-economic variables was one important character of changes in different land space. The trade-offs and synergies of multiple functions for land space are significant for sustainable ecosystem management.